Me, Myself, and I: Self-Centeredness, FOMO, and Social Media Use - David, Meredith E.; Roberts, James A. (Canadian journal of behavioural science, 2024)
The present research investigates the relationship between self-centeredness and social media use and suggests that fear of missing out (FOMO) is a key mechanism underlying this relationship. Three studies were conducted to test these relationships, including a survey (Study 1, n = 199 U.S. adults) and two experiments, including one where self-centeredness is manipulated (Study 2, n = 241 U.S. adults) and another where FOMO is primed (Study 3, n = 102 U.S. adults). It appears that self-centred individuals use social media more to assuage their FOMO than to bolster their self-centric worldview. The study results provide consistent evidence which could refute prior theory and explanatory processes. Contrary to self-construal theory, which would suggest that individuals with an independent self-construal (more self-centred) would be less likely to experience FOMO, present results suggest otherwise. Additional study contributions include the use of two experimental designs to assess the direction of causal flow between self-centeredness, FOMO, and social media use. La présente étude examine la relation entre l'égocentrisme et l'utilisation des médias sociaux et suggère que la peur de passer à côté de quelque chose (FOMO) est un mécanisme clé qui sous-tend cette relation. Trois études ont été menées pour tester ces relations, notamment une enquête (étude 1, n = 199 adultes américains) et deux expériences, dont une où l'égocentrisme est manipulé (étude 2, n = 241 adultes américains) et une autre où la peur de passer à coté de quelque chose est amorcée (étude 3, n = 102 adultes américains). Il semble que les individus égocentriques utilisent les médias sociaux davantage pour apaiser leur peur de passer à côté de quelque chose que pour renforcer leur vision égocentrique du monde. Les résultats de l'étude fournissent des preuves cohérentes qui pourraient réfuter les théories et les processus explicatifs antérieurs. Contrairement à la théorie de l'autoconstruction, qui suggère que les individus ayant une autoconstruction indépendante (plus égocentriques) seraient moins susceptibles d'être victimes de la peur de passer à côté de quelque chose, les présents résultats suggèrent le contraire. D'autres contributions à l'étude comprennent l'utilisation de deux modèles expérimentaux pour évaluer la direction du flux causal entre l'égocentrisme, la peur de passer à côté de quelque chose et l'utilisation des médias sociaux. Public Significance Statement Conventional thinking would suggest that self-centred people use social media to "feed their egos." The present research, however, finds that self-centred individuals use social media to assuage their fear of missing out (FOMO) rather than to bolster their self-centric worldview. Results across three studies suggest self-centred individuals approach social media use from a point of weakness more so than from a point of strength.